Penyelesaian Kasus Tindak Pidana Anak Melalui Diversi Dalam Perspektif Sistem Peradilan Pidana Anak - Azhary Ramadhan; Kamarusdiana Kamarusdiana; Soefyanto Soefyanto (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This study aims to determine the application of restorative justice in Indonesia in child criminal cases. This study aims to answer whether the principles of restorative justice can be applied in Indonesia with the prevailing legal system, as well as to answer whether the application of diversion against juvenile justice in Indonesia is in accordance with the principles of restorative justice. This research is a normative legal research using the statue approach or the law approach with primary data sources, namely the Law on the Juvenile Criminal Justice System Number 11 of 2012, with data processing based on data on the application of diversion in Indonesia, then analyzed in the form of statements and diagrams. This study uses the theory of Lawrence M. Friedman which is associated with Islamic law, as well as the theory of Restorative Justice and the theory of legal benefits. The results showed that the application of restorative justice in Indonesia found that law enforcers in implementing diversion were still quite low, because according to records there were still many law enforcers at the level of the police, prosecutors and courts who had not been effective in implementing diversion in juvenile justice.Keywords: Restorative Justice, Diversion, Children Facing the Law